2011
DOI: 10.11606/issn.1981-0490.v14i1p73-91
|View full text |Cite
|
Sign up to set email alerts
|

A empregabilidade das pessoas com deficiência: uma análise da inclusão social no mercado de trabalho do município de Bauru, SP

Abstract: Amparada nos preceitos da inclusão social, esta pesquisa objetivou examinar a empregabilidade das pessoas com deficiência (PCD) em atendimento ao Decreto 3.298, que estabelece cotas para contratação de PCD para empresas com 100 ou mais funcionários. Foram entrevistados funcionários do setor de recursos humanos de 12 empresas de médio e grande porte de um município do oeste paulista, à luz de um roteiro estruturado. As entrevistas foram integralmente transcritas, categorizadas pelo critério da análise de conteú… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
26

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 2 publications
1
15
0
26
Order By: Relevance
“…We emphasize that the criterion commonly established by companies for hiring is completion of High School (RAIS, 2016); thus, to perform the duties in existing positions, the candidate must have mastery of reading, writing and elementary calculation. This is an understandable and even low requirement nowadays when access to information and education is facilitated; however, what is worrying is that this requirement is hardly met when it comes to people with intellectual disabilities, and it is, therefore, the biggest justification for entrepreneurs not to hire them (Araújo & Schimidt, 2006;Tanaka & Manzini, 2005;Veltrone & Almeida, 2010;Violante & Leite, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…We emphasize that the criterion commonly established by companies for hiring is completion of High School (RAIS, 2016); thus, to perform the duties in existing positions, the candidate must have mastery of reading, writing and elementary calculation. This is an understandable and even low requirement nowadays when access to information and education is facilitated; however, what is worrying is that this requirement is hardly met when it comes to people with intellectual disabilities, and it is, therefore, the biggest justification for entrepreneurs not to hire them (Araújo & Schimidt, 2006;Tanaka & Manzini, 2005;Veltrone & Almeida, 2010;Violante & Leite, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…The employability of persons with disabilities in 12 midsize and large enterprises in a town west of São Paulo has been the subject of research by Violante & Leite (2011), which results showed that only a third of private companies comply with the law. Business policies in the context studied prioritize hiring people whose disabilities do not require structural modifications or that represent a favorable aspect to the production.…”
Section: The Brazilian Legislation For Persons With Disabilities and mentioning
confidence: 99%
“…The disabled person is entitled, on an equal basis with other persons, to just and favorable conditions of work, including equal remuneration for work of equal value (Brasil, 2015, p. 1) In Brazil, there is much interest in discussing diversity emphasizing the insertion of professionals with disabilities to the workplace. Some studies aimed at identifying the facilities and difficulties of the persons to be inserted and remain in the labor market (Hoffmann et al, 2013;Simonelli & Camarotto, 2011;Violante & Leite, 2011;Oliveira et al, 2009;Ribeiro & Carneiro, 2009;Moraes de Souza, 2009;Rodrigues et al, 2009;Carvalho-Freitas, 2009;Carvalho-Freitas & Marques, 2007).…”
Section: The Inclusion Of Professionals With Disabilities: Some Discumentioning
confidence: 99%
“…A princípio, como mostrado em pesquisas (Bahia, 2006;Carvalho-Freitas, 2007;Correr 2010;Dota 2015;Simas, Souto, & Carvalho-Freitas, 2014;Violante, & Leite, 2011), muitas empresas apenas passaram a contratar pessoas com deficiência devido à legislação de cotas vigente, objetivando a evitação de multas ou outras formas de punição, sem buscar, portanto, compreender as reais possibilidades, potencialidades e dificuldades apresentadas por esses sujeitos, e como elas poderiam contribuir para o desenvolvimento de seu empreendimento; o que tem, em síntese, culminado em práticas de inserção e não da sua real participação, como afirma Camargo (2014).…”
Section: Considerações Sobre a Identidade E O Papel Do Pot Diante Do unclassified